Stagflation substantiation as an indication of systemic crisis in the financial sector of the economy - Zherdetska, Liliia (Technology audit and production reserves, 2017)
It is established that the quantitative indicators for the systemic transformation crisis in the economic literature are not determined, given their complexity and uniqueness for national economies. It is possible to identify the presence of an episode of a systemic transformation crisis using the stagflation indicator. According to the object of the presented research are the processes of identification of stagflation phenomenon. The method of threshold values (for identifying episodes and determining the depth of stagflation) is used to generalize and compare (to assess the similarities and differences in the dynamics of stagflation processes among groups of countries). Estimating the depth of stagflation has several advantages over the identification of episodes: 1) allows a quantitative comparison of the negative impact of stagflation; 2) neutralizes the main problem of identifying episodes of stagflation – the need to use different criteria depending on economic development (that is, it is possible to compare the results of evaluation to different groups of countries). The indicators of the depth of stagflation by groups of countries are calculated: developed countries (1980–2017), developing countries (1980–2017), incl. post-Soviet countries (1993–2017). It is established that in modern conditions the phenomenon of stagflation is more typical for developing countries. A significant contribution to the depth of stagflation processes is caused by inflation, which high rates are primarily characterized by transitive economies and developing ones. The depreciation of the national monetary unit causes the deployment of inflationary processes, and if inflation exceeds a certain level, economic growth is almost impossible, which causes the phenomenon of stagflation in transitive economies. The solution of the problem of absorption of negative consequences of systemic crises in Ukraine is in the sphere of ensuring sustainable economic growth. Maintaining export-oriented industries, eliminating structural imbalances in the economy, reducing the level of external debt and ensuring innovative development will contribute to such growth